Hindi Language Competency of KGBV Students in Bihar - Singh, Chandra B. P.; Singh, Ravi Shankar (INDIAN EDUCATIONAL REVIEW, 2017)
The study identified some reasons of poor performance (about 40 per cent) in Hindi language of Class VI students in KGBV of Bihar and also noticed loss in transition (about 6 to 24 per cent) at the upper primary level despite residential facilities being provided to them. There existed acute shortage of teachers (46 per cent) as well as wardens (46 per cent) in KGBV, resulting in poor management of residential facilities. Additionally, non-availability of language teacher for teaching Hindi and their limited understanding of pedagogical processes left the teaching-learning transaction unattended. Their insufficient training to language at the time of induction showed a gap in inputs what they desired and what they had. In some KGBVs (e.g., Kishanganj) there existed minimal activities to overcome learning deficiencies in Hindi. They had virtually no idea about how to evaluate students and formulate plan for improving Hindi language. Illiterate mothers had a strong desire to educate their daughters (40 per cent achievement in Hindi language). Attitudinal problem of the school teachers and headmasters were the prominently observed. They attributed to the KGBV stakeholders for the managerial activities. The study suggested deployment of teachers and their intensive training for improving Hindi language.